PBL and PJBL Comparative Study on Critical Thinking Ability in Blended Learning - Nunung Lusiana; Herwin; Laila Fatmawati (Universitas Pendidikan Ganesha, 2022)
IPS learning is boring, and students lack enthusiasm which results in a decrease in students’ critical thinking skills. This study aims to analyze the application of the PBL and PJBL models to necessary thinking skills in blended learning. This research is a type of quantitative research with experimental methods. The research design used was the Matching Pretest Posttest Control Grub Design. The population of this study was 320, and the sample was 76. The sampling technique used a random sampling technique. The method used to collect data is observation and tests. The instrument used to collect information is the question sheet. The data analysis technique was carried out using the t-test and ANOVA test using the SPSS 25 application. The result of the analysis showed that the problem-based learning model increased the mean before and after treatment. The application of project-based learning has an average rise before and after being given treatment. Comparing problem-based learning and project-based learning models on critical thinking skills shows that the use of problem-based learning models is superior to the use of project-based learning models. This study concludes that both models influence crucial thinking skills and that using problem-based learning models is superior in increasing necessary thinking skills compared to using project-based learning models.